The mediating role of customer loyalty on the effect of celebrity endorsement to impulse buying behavior - Asakdiyah, Salamatun; Bonaga, Jason Keith; Maheswari, Uma; Prastowo, Indro; Salampessy, Andy Passyada (Jurnal Fokus Manajemen Bisnis, 2024)
Consumer behavior in purchasing products can be influenced by various internal and external factors. Both these factors can encourage individuals to purchase a product suddenly or unplanned in advance. The factors that allegedly influence consumers’ impulse buying are celebrity endorsements and customer loyalty. This study analyzes the effect of celebrity endorsements on impulse buying behavior by mediating customer loyalty. This research used Lazada's e-commerce service in Yogyakarta with a total of 80 respondents. The data obtained were then processed using the Smart PLS application in the form of validity, reliability, and direct and indirect hypothesis tests. Based on the results of the data processing, it can be concluded that the four research hypotheses are accepted. Celebrity endorsements have been shown to have a positive effect on impulse buying behavior, celebrity endorsements have been shown to have a positive effect on customer loyalty, customer loyalty has a positive effect on impulse buying behavior, and customer loyalty has been shown to mediate celebrity endorsement relationships and impulse buying behavior.